(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
Spheroidization annealing of a low carbon steel and its effects on the microstructure and mechanical properties of dual phase (DP) steel were studied. It was revealed that the reduction in strength and hardness of the quenched martensitic microstructure is much more pronounced compared with the full annealed ferritic-pearlitic banded microstructure as the spheroidizing time goes on. This was related to the confinement of spheroidized carbide particles to distinct bands in the latter but uniform dispersion of carbides and high-temperature tempering of martensite in the former. During intercritical annealing of the spheroidized microstructures, the tendency to obtain spheroidized martensite particles as discrete islands was observed. This, in turn, resulted in inferior strength-ductility balance compared with the DP steel obtained from the intercritical annealing of martensite, which negates the usefulness of the spheroidized microstructures as the initial microstructures for processing of DP steels.